Keadilan Menurut Perspektif Amos dan Impementasinya Bagi Gereja Masa Kini - Maria Kristina Simarmata; Elisamark Sitopu; Warseto Sihombing (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study is to investigate the concept of justice according to Amos's perspective and how to identify concrete methods of its implementation for the church today. This research uses Thematic Method with literature study, to analyze relevant texts from the Book of Amos in the Bible. The analysis focused on identifying central themes related to justice from Amos' perspective. In addition, the research also incorporates relevant theological and social literature to understand the context of the implementation of the principles of justice of Amos in the modern church. The results revealed that Amos emphasized the importance of social justice, rejection of economic injustice, and an active role in combating oppression in society. Implementation of these principles in today's church involves a variety of actions, including proactive social service, advocacy for structural change, and education of church members on issues of justice